The signature of all things - Gilbert, Elizabeth, 1969- (New Delhi : Bloomsbury, 2013)
""Spanning much of the eighteenth and nineteenth centuries, the novel follows the fortunes of the extraordinary Whittaker family as led by the enterprising Henry Whittaker--a poor-born Englishman who makes a great fortune in the South American quinine trade, eventually becoming the richest man in Philadelphia"". --
Keywords: Enlightenment -- Fiction; Industrial revolution -- Fiction; Painters -- Fiction; Women botanists -- Fiction; Historical fiction